P55 TARGET ORGAN DAMAGE AND BLOOD PRESSURE VARIABILITY IN HYPERTENSION - Dimitrios Terentes-Printzios (Artery Research, 2017)
Purpose/Background/Objectives: Hypertension is associated with several markers of subclinical target organ damage (TOD). Short-term blood pressure variability (SBPV) is a prognostic factor for cardiovascular events in hypertensives. We hypothesised that there is a relationship between SBPV and TOD in never-treated hypertensives. Methods: We enrolled 943 consecutive essential hypertensives (mean age 53±12 years, 497 males). Markers of subclinical TOD [left ventricular mass index (LVMI), pulse wave velocity (PWV), total arterial compliance (TAC), aortic augmentation index (AIx@75), ankle-brachial index (ABI) and estimated glomerular filtration rate (eGFR)] and 24-h ambulatory blood pressure were evaluated in all patients. SBPV was calculated as follows: 1) SD of 24-hour, daytime, or nighttime SBP and 2) weighted SD of 24-hour SBP. Results: In multivariable regression analysis, all four variables of SBPV exhibited significant association with LVMI (p = 0.014, p = 0.002, p = 0.002 and p < 0.001, respectively), PWV (p = 0.021, p = 0.015, p = 0.055 and p = 0.006, respectively) and TAC (p = 0.048, p = 0.020, p = 0.036 and p = 0.006, respectively). In multivariable analysis, ABI and eGFR were not associated with indices of SBPV. We assessed TOD based on 2013 European Guidelines for Hypertension [left ventricular hypertrophy (LVMI > 115 g/m2 in men and >95 g/m2 in women), increased PWV (PWV > 10m/s), increased AIx@75 (AIx@75 > 28%), decreased ABI (ABI < 0.9) and decreased renal function (eGFR < 60ml/min)]. In multivariable logistic regression analysis, SBPV indices were not associated with markers of TOD (P > 0.05). Conclusions: Our findings support a complex relationship between SBPV and TOD in hypertension. Specifically, SBPV is more closely related to markers of ventricular and vascular compliance than other markers of TOD in hypertension.